The abuse of process doctrine in the Anglo-Saxon system: A reconstruction at the antipodes of the european system. - Liakopoulos, Dimitris (Revista Eletrônica de Direito Processual, 2025)
ABSTRACT: The present survey is based on the analysis of the abuse process in the common law system, in particular in the system of the United States. Looking at the Anglo-Saxon system, the overall theoretical abuse of process is based on the principle of fairness: if a fair trial cannot take place, or it would be unfair to continue a criminal trial against anyone, the basic concept is that we are facing a "false" process. The accused is no longer in a position to exercise his faculties and rights fully. To continue would be an outrage against the moral integrity of the system and, at the same time, unjustly trying to at least provide a "hard" and essential guarantee core, to protect the overall fairness of the proceeding which, therefore, would represent the final horizon towards which every (procedural) means is projected.